2009
DOI: 10.1055/s-0029-1211273
|View full text |Cite
|
Sign up to set email alerts
|

Effects of music treatment on salivary cortisol in patients exposed to pre-surgical stress

Abstract: The response of the adrenal cortex to a stressor consisting of information about a surgery to be performed the following day was studied in 34 patients by monitoring changes in salivary cortisol. From those, 18 patients were subjected to an individually selected 1 h music program, applied immediately following receipt of the information, and the remaining 16 patients formed a reference group. Another 10 patients, not awaiting surgery, served as controls. Saliva was sampled before the stressor and 5 more sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
1
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 7 publications
6
38
1
4
Order By: Relevance
“…Music is a powerful tool in evoking emotions and, by extension, listening to music can be explored for reducing the negative effects of stress. Supportive evidence can be found in the observation that listening to music resulted in a marked reduction in salivary cortisol levels in patients exposed to pre-surgical stress, both in a medical (Miluk-Kolasa et al, 1994) and in a nonmedical setting (Khalfa et al, 2003). These experiments suggested that relaxing music is more effective than silence in decreasing cortisol levels after stress induction.…”
Section: Introductionmentioning
confidence: 83%
“…Music is a powerful tool in evoking emotions and, by extension, listening to music can be explored for reducing the negative effects of stress. Supportive evidence can be found in the observation that listening to music resulted in a marked reduction in salivary cortisol levels in patients exposed to pre-surgical stress, both in a medical (Miluk-Kolasa et al, 1994) and in a nonmedical setting (Khalfa et al, 2003). These experiments suggested that relaxing music is more effective than silence in decreasing cortisol levels after stress induction.…”
Section: Introductionmentioning
confidence: 83%
“…All patients in the intervention group listened to sedative instrumental music with a slow tempo, with 60-80 beats/minute, which had been reported to be calming and relaxing (MilukKolasa et al, 1996;Miluk-Kolasa et al, 1994). The music was played on a CD player with earphones so the patients would not be disturbed by any other sounds and the physician and the nurses would not be disturbed by the music.…”
Section: Interventionmentioning
confidence: 99%
“…Several clinical studies have reported reductions in salivary cortisol levels after behavioral interventions to reduce stress (Aboulafia-Brakha, Suchecki, Gouveia-Paulino, Nitrini, & Ptak, 2014;Galvin, Benson, Deckro, Fricchione, & Dusek, 2006;Miluk-Kolasa, Obminski, Stupnicki, & Golec, 1993). Specifically, saliva contains free, biologically active cortisol as opposed to total cortisol present in serum or plasma.…”
Section: Introductionmentioning
confidence: 99%